Evaluating pre-sowing treatments to enhance germination and early growth of the threatened Sterculia villosa Roxb. in Bangladesh (Bangladesh Journal of Plant Taxonomy, 2025)
Elephant rope (Sterculia villosa Roxb.)  is a threatened plant species in Bangladesh. To conserve this threatened tree, research should be carried out on improvement of germination and early growth. Therefore, the objective of the study was to explore the effects of pre-sowing seed treatments on germination behavior and to assess the possibility of increasing the germination rate of Sterculia villosa. The seeds were subjected to nine pre-sowing treatments viz., T0: Seeds with no treatment (Control), T1: Seeds scrapping with sand paper at the distal end, Seeds immersed in T2:  room temp. water for 24 hours, T3: hot water for 1 minute, T4: 10% concentrated H2SO4 for 1 minute, T5: 10% concentrated H2SO4 for 3 minutes, T6: 10% concentrated HCL for 1 minute, T7: 10% concentrated HCL for 3 minutes, T8: 200ppm GA3 for 24 hours, T9: Fungicide (Autostin 50 WDG) for 24 hours. The study conducted in the propagation house, revealed that pre-sowing treatments significantly (p